Evaluating the Importance of Factors Effecting the Consumer Behavior in new Dialysis Machine in Iran-Tehran - Tabatabaei , Seyed Mahameddin; Mirabi , Vahid Reza; Afshar Kazemi, Mohammad-Ali; Fares, Foroozan (Journal of Pediatric Nephrology, 2020)
Background and Aim: The health care industry is very critical base on its relation to human life. The amount of research and changes in the diagnostic techniques and procedures, therapeutic techniques, drugs and equipment are very vast and fast. In order to prevent the waste of resources, it is required to understand the needs and wants of the market. Therefore, it is very crucial to understand the patient’s opinion. Methods: By reviewing the literature of consumer behavior theories, a number of factors are classified into seven categories. Based on this classification a questionnaire was developed. The main respondents were parents of a child who is suffering from renal failure. Then, two statistical tests were held using t-test in order to identify the importance and prioritizing of each factor also correlation coefficient to understand the availability and strength of relationship among factors. Results: The results base on the statical tests indicates that the three groups of factors do not affect consumer behavior. The rest of the factors have an influence on consumer behavior regarding a new product. Base on the result hospitals and clinics that have hemodialysis sections with the specialty of delivering service to children should recognize the product accuracy, the lowest possible price, with vast of informative activity to parents and the children and doctors. Conclusion: These approaches will smooth the way for hospitals and clinics to launch new services to renal failure patients.